2004
DOI: 10.1016/j.neuropsychologia.2004.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Visual paired comparison performance is impaired in a patient with selective hippocampal lesions and relatively intact item recognition

Abstract: In this study, we have examined visual recognition memory in a patient, YR, with discrete hippocampal damage who has shown normal or nearly normal item recognition over a large number of tests. We directly compared her performance as measured using a visual paired comparison task (VPC) with her performance on delayed matching to sample (DMS) tasks. We also investigated the effect of retention interval between familiarisation and test. YR shows good visual recognition with the DMS task up to 10 s after the fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 42 publications
6
53
0
Order By: Relevance
“…This result suggests that extrahippocampal areas may be support the expression of novelty preferences in the short term, but that the hippocampus is critical when delayed recognition is required (Nelson, 1995). These results are also consistent with data from adult amnesics showing that the effect of hippocampal damage is most apparent during delayed VPC testing (McKee & Squire, 1993;Pascalis et al, 2004).…”
Section: Visual Paired-comparison Tasksupporting
confidence: 87%
See 2 more Smart Citations
“…This result suggests that extrahippocampal areas may be support the expression of novelty preferences in the short term, but that the hippocampus is critical when delayed recognition is required (Nelson, 1995). These results are also consistent with data from adult amnesics showing that the effect of hippocampal damage is most apparent during delayed VPC testing (McKee & Squire, 1993;Pascalis et al, 2004).…”
Section: Visual Paired-comparison Tasksupporting
confidence: 87%
“…For example, Nemanic, Alvarado, and Bachevalier (2004) showed that monkeys with lesions to the hippocampus who were impaired on the VPC task did not exhibit impairments on a delayed nonmatching to sample (DNMS) task. Patients with damage to medial temporal lobe systems also show impaired VPC performance but relatively intact recognition (McKee & Squire, 1993;Pascalis et al, 2004). These results suggest that the hippocampus may be critical for the expression of novelty preferences specifically, rather than performance on visual recognition tasks generally.…”
Section: Visual Paired-comparison Taskmentioning
confidence: 86%
See 1 more Smart Citation
“…YR's memory performance has been reported extensively (Mayes et al, 2001(Mayes et al, , 2004Holdstock, Mayes, Roberts et al, 2002), and is briefly summarised here. Her current FSIQ (WAIS-R; Wechsler, 1981), measured at the time of scanning, was in the average range (FSIQ 102 Five control participants were recruited.…”
Section: Percent Time Looking At Each Stimulus During the Two Recognimentioning
confidence: 97%
“…The visual paired comparison task (VPC) exploits a subject's natural tendency to look preferentially at novel stimuli relative to familiar stimuli. VPC task performance has been found to be sensitive to damage to the hippocampal formation in both amnesic patients (McKee & Squire, 1993;Pascalis et al, 2004) and adult monkeys (Pascalis & Bachevalier, 1999;Zola et al, 2000;Nemanic et al 2004) when increasing delays were used. In the present experiment, we manipulated the backgrounds onto which the objects appeared such that in some trials the backgrounds were identical during familiarization (study) and test, but on other trials they differed between familiarization and test (See Figure 1).…”
Section: Introductionmentioning
confidence: 99%